Fuse or die: Shaping mitochondrial fate during starvation - Rambold, Angelika S. (Landes Bioscience, 2011)
Mitochondria continuously change their shape and thereby influence different cellular processes like cell death or development. Recently, we showed that during starvation mitochondria fuse into a highly connected network. The change in mitochondrial shape was dependent on inactivation of the fission protein Drp1, through targeting of two different phosphorylation sites. This rapid inhibition of mitochondrial fission led to unopposed fusion, protecting mitochondria from starvation-induced degradation and enabling the cell to survive nutrient scarce conditions.